BENGKEL SASTRA BALAI BAHASA DIY DALAM PERSPEKSTIF SOSIOLOGI PIERE BOURDIEU - Zamzuri, Ahmad (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2016)
Yogyakarta in Indonesia literature is one of the literary arenas that are unseparated from prominent literary writers in Indonesia, such as Korrie Layun Rampan, WS. Rendra, Emha Ainun Nadjib, etc. Those writers are associated to literature community surrounding, such as Korrie Layun Rampan and Emha Ainun Nadjib whose were members of Persada Studi Klub (PSK) in 1969-1977 era. After PSK had dismissed, many literary community appeared to enlighten literary atmosphere in Yogyakarta. In 2000s, Studio Pertunjukan Sastra (SPS) and Sastra Bulan Purnama (SBP) appeared with different ways and styles in activating and appreciating literary works. Before those communities appeared, in 1996, a program (community) had born named Bengkel Sastra (BS) in the initiative of Balai Penelitian Bahasa Yogyakarta (now Balai Bahasa DIY). Bengkel Sastra (BS) offers creative process with applied practices in writing and oral expression through literary performance. BS becomes arena of modal transfer from tutor to participants. The transfer modal enable modal investment of BS’s participants in preparing them to be writers in future. This research will focus on modal exchange, agent, and legitimate in BS. To explain those matters, this research used sociology theory of Pierre Bourdieu, particularly modal exchange and legitimate in agents in BS. This research is descriptive. The result shows that BS offers legitimate to agent (participants), although little, to enter literary world through celebrating works (books), and literary works performance orally.